ADVANTAGES AND DISADVANTAGES OF THE TECHNOLOGY FOR DETERMINING THE NUCLEOTIDE SEQUENCE OF DNA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the main advantages and disadvantages of the technology of different generations of DNA sequencing. The main innovative ideas in the evolution of sequencing technology.